Legal Strength of A Peace Deed Made Before A Notary In Dispute Resolution Out of Court - Dini Septiani; Harmono Harmono; Jaenudin Umar (Ann Publisher, 2026)
Background. The option to resolve disputes out of court is increasingly being used, especially when parties want a quicker, less protracted process. In practice, peace agreements are often expressed as deeds executed before a notary in the hope of achieving greater legal force. The problem is that this power is not always directly proportional to the effectiveness of its implementation. When an agreement is violated, the peace deed cannot be used directly to enforce the obligation; it must be brought back to court. At this point, a fundamental problem arises regarding the position and effectiveness of the notarial peace deed in the civil law system. Aims. This research is directed at examining further the legal position of the peace deeds, how the evidentiary force operates, and what happens when the agreement is not implemented. Methods. The approach used is normative, examining relevant laws, regulations, and legal concepts, as well as associated practices. Result. From the results of the analysis, it can be seen that the notarial peace deed is in a position that is not completely single. It has the power of an authentic deed recognized in the proof, but at the same time it still depends on the logic of the agreement, whose execution is determined by the parties. The power of proof does provide certainty about what has been agreed, but it does not necessarily guarantee that the agreement will be implemented without dispute. When a default occurs, the deed serves more as a basis for proof in a new lawsuit than as a tool to enforce it directly. Conclusion. This condition shows that the notarial peace deed is not fully capable of serving as a final instrument for dispute resolution. Therefore, efforts are needed to strengthen its position not only in the evidentiary aspect but also in bridging the implementation of the agreement, so that the goal of resolving disputes outside the court can truly be achieved.